2014
DOI: 10.1007/s00776-013-0495-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary frozen shoulder: brief review of pathology and imaging abnormalities

Abstract: BackgroundPrimary frozen shoulder (FS) is a painful contracture of the glenohumeral joint that arises spontaneously without an obvious preceding event. Investigation of the intra-articular and periarticular pathology would contribute to the treatment of primary FS.Review of literatureMany studies indicate that the main pathology is an inflammatory contracture of the shoulder joint capsule. This is associated with an increased amount of collagen, fibrotic growth factors such as transforming growth factor-beta, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 25 publications
2
89
1
8
Order By: Relevance
“…It is characterized by shoulder pain and limitation in range of motion (ROM) (Neviaser and Hannafin, 2010). Many studies have attempted to determine the pathophysiology of frozen shoulder and the best treatment modality (Bunker et al, 2000;Uhthoff and Boileau, 2007;Tamai et al, 2014). Fibrosis and contracture of the joint capsule, preceded by synovitis are known symptoms of frozen shoulder.…”
Section: Introductionmentioning
confidence: 98%
“…It is characterized by shoulder pain and limitation in range of motion (ROM) (Neviaser and Hannafin, 2010). Many studies have attempted to determine the pathophysiology of frozen shoulder and the best treatment modality (Bunker et al, 2000;Uhthoff and Boileau, 2007;Tamai et al, 2014). Fibrosis and contracture of the joint capsule, preceded by synovitis are known symptoms of frozen shoulder.…”
Section: Introductionmentioning
confidence: 98%
“…Most likely, a sequential pathologic process from synovial inflammation to capsular fibrosis is the main source of pain and limited motion in frozen shoulder [2, 3, 5, 912]. Rodeo et al [3] reported that a hypervascular synovial hyperplasia was present in the early stages, and resulted in eventual fibrosis in the subsynovium and capsule.…”
Section: Introductionmentioning
confidence: 99%
“…Lefevre-Colau and al [30] showed a good interobserver agreement for the thickness of the articular capsule at the axillary recess. According to Watson and al [22], arthroscopic inflammatory changes occur in the posterior and anterior recesses with obliteration secondary to scar tissue deposition [24], [31]. However, in the literature the association of a narrow axillary recess to a thickened joint capsule is not always recognized.…”
Section: Discussionmentioning
confidence: 99%
“…These include increased thickness of capsulosynovial structures [14], [15], [16], [19], a decreased width or volume of the recess [16], [19], [20], as well as contrast enhancement and increased signal intensity of the inferior glenohumeral ligament on T2 sequences [18]. These imaging features of AC have been correlated to arthroscopic and histological findings [21], [22], [23], [24].…”
Section: Introductionmentioning
confidence: 94%